Term Relationships and Their Contribution to Text Semantics and Information Literacy Through Lexical Cohesion - Morris, Jane; Beghtol, Clare; Hirst, Graeme (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
An analysis of linguistic approaches to determining the lexical cohesion in text reveals differences in the types of lexical semantic relations (term relationships) that contribute to the continuity of lexical meaning in the text. Differences were also found in how these lexical relations join words together, sometimes with grammatical relations, to form larger groups of related words. . .